2015
DOI: 10.1111/gfs.12197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grass silage feed value on feed intake and performance of pregnant and lactating ewes and their lambs

Abstract: Effects of grass silage feed value on intake, dietary sorting, body condition (BC) and body weight (BW) of pregnant and lactating ewes and on liveweight gain (LWG) of their suckling lambs were evaluated. Twin‐bearing ewes were fed ad libitum grass silage of (i) high feed value (HFV), (ii) medium feed value (MFV) and (iii) low feed value (LFV), plus 0·8 kg concentrate in late pregnancy and lactation. The HFV, MFV and LFV silages contained 11·7, 10·8 and 9·3 MJ metabolizable energy (ME) kg−1 DM respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…According to Van Soest (1994), advanced stage of maturity at harvest increases the contents of NDF and lignin, and the ADL:NDF ratio in forage cell walls, decreasing the digestibility (Allen, 2000;Rustas et al, 2011). Harvesting grasses at early maturity stages increases the forage energy value for ruminants by decreasing the fiber concentration and increasing fiber digestibility and the CP concentration (Nadeau et al, 2016a). In the present study, grass and barley silage at an early maturity stage showed greater IVOMD than its counterpart harvested at late maturity stage, and also greater in vivo digestibility of DM and of all nutrients investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Van Soest (1994), advanced stage of maturity at harvest increases the contents of NDF and lignin, and the ADL:NDF ratio in forage cell walls, decreasing the digestibility (Allen, 2000;Rustas et al, 2011). Harvesting grasses at early maturity stages increases the forage energy value for ruminants by decreasing the fiber concentration and increasing fiber digestibility and the CP concentration (Nadeau et al, 2016a). In the present study, grass and barley silage at an early maturity stage showed greater IVOMD than its counterpart harvested at late maturity stage, and also greater in vivo digestibility of DM and of all nutrients investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Harvesting grasses for silage at early maturity stages are known to increase OM digestibility (OMD), intake, and performance of ewes (Nadeau et al, 2016a). Because of the accumulation of digestible starch during grain filling postheading, the OMD of whole-crop cereals remains relatively constant after milk stage of maturity (Rustas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in order to increase yields in production systems with ruminants, increased forage quality through, e.g. optimising ley harvesting times (Nadeau et al 2015) would be more favourable for promoting soil fertility than introducing higher concentrate proportions.…”
Section: Soil Fertilitymentioning
confidence: 99%
“…Improved forage quality makes it possible to use high proportions of forage (e.g. 60-70% of total dietary dry matter) even for high-yielding cattle (Patel 2012;Nadeau et al 2015;Johansson et al 2016). Cows fed forage-based diets up to seven lactations showed no negative development in terms of production efficiency with age, older cows were even able to ingest more (Grandl et al 2016).…”
Section: Animal Health and Welfarementioning
confidence: 99%
“…Grazed grass is the most economical feed source for sheep in temperate regions of the world [1,2], however, climatic conditions limit grass growth during the winter months [3][4][5]. During this winter period, ewes in Ireland and elsewhere are often housed and offered conserved forage, predominantly grass silage [6][7][8], despite grass silage frequently being incapable of meeting the nutrient requirement of ewes, especially multiple bearing ewes, during late pregnancy [9,10]. Inadequate nutrient intake at this stage of the production cycle, which coincides with increased nutrient demand to support foetal development, can result in reduced colostrum production, milk production potential, and ewe body condition [11], and such periods of nutritional restriction may result in reduced lamb performance postpartum [12].…”
Section: Introductionmentioning
confidence: 99%